The Plight of Reptiles as Ecological Actors in the Tropics - de Miranda, Everton B. P. (Frontiers in Ecology and Evolution, 2017)
Earth’s tropical ecosystems have witnessed several extinctions and a dramatic reduction of the range and abundance of large reptile species, which is directly related to the rise of early and modern humans. The ocurrence of such extinctions, range reduction, species loss and the consequences for several paramount ecosystem processes are poorly documented compared to other large vertebrate species. Here, I reviewed the literature on the ecological processes performed by large tropical reptile species and their human-induced widespread demise in order to determine knowledge gaps and encourage a paradigm shift in understanding on the interactiveness of such species. The interactions and species involved indicate that large abundant reptiles in the tropics are important in ecological processes, and can consequently have an important role in ecosystem function through gene dispersal, nutrient cycling, trophic action and ecosystem engineering. These important interactions performed by reptiles are not solely performed by few species, or geographically restricted to islands, but instead present a pattern that repeatedly occurs in large reptiles distributed over tropical ecosystems. The observed tendency of reptiles to be tightly involved in these ecological interactions has important implications for the ecology of tropical ecosystems. Lost and current ecological processes performed by large reptiles may be orders of magnitude higher than what is currently perceived, and the misleading baseline of those processes must be addressed otherwise we risk losing species and services that are dependent of such interactions. To fix this bias I suggest: (a) Increase information spreading about Pleistocene-Holocene reptile extinctions using popular media; (b) Improved exchange between the research field of megafauna effects in ecosystems and herpetologists working with large reptiles; (c) Increase research effort on anthropogenic reptile extinctions and their potential to predict future losses; (d) Address the knowledge gaps, as human-reptile conflict, chelonian seed dispersal and nutrient movement; (e) Increase quantitative research on large reptile population ecology, density, and abundance. (f) address the potentially present or lost ecosystem effects of extant and extinct reptile species. Although the importance of reptiles in most tropical ecosystems has been perceived as negligible, this study shows that this may be a misleading paradigm.